Revisiting Pedagogic Practices: a case for Sustainable Learning Environments for postgraduate supervision studies in Higher Education - Nkoane, Molebatsi Milton (South African Journal of Higher Education, 2016)
This article aims to encourage a radical and democratic approach towards supervision of postgraduate studies in institutions of higher education. This article further amplifies the notion of sustainable learning environments, where we use our privileged positions to create opportunities for learning and advancement of others. The article valorises the sentiments of sustainable learning environments for a rejuvenated sense of agency and democratic citizenry with fresh lenses to interrogate our own pedagogic practices in higher education. A theoretical framework adopted in this article views sustainable learning environments as a contestation of marginalisation and demystifying the notion of ‘experts’. Sustainable learning environments are then seen as enabling and empowering environments for postgraduate studies. This kind of learning environments or pedagogic practices provides opportunities for critical engagements, creativity and negotiated pedagogic practices. The article concludes by demonstrating how sustainable learning environments create a collaborative team approach and encourage transparency and inclusion in leading to quality research process and outcomes. KEYWORDS: Pedagogic practices; Sustainable learning environments; Empowerment; Postgraduate supervision; and Higher Education.